Coping with climate change through air pollution control: some legal initiatives from Malaysia - Mustafa, Maizatun; Syed Abdul Kader, Sharifah Zubaidah; Sufian, Azlinor (2012)
Malaysia is committed to addressing climate change and has taken various initiatives in dealing with the matter. At the policy level, the policy makers are charged with identifying possible national response strategies to climate change and implementing them through various tools. One of the focus areas is the regulation of the green house gasses emissions from various sources, including that of industries and motor vehicles. During the past years, Malaysia has introduced a number of emission control measures to deal with air pollution, particularly through the enforcement of environmental law. This paper sets out a range of existing legal strategies on the control of air pollution from both stationary and mobile sources. The objective is to identify how air pollution law in Malaysia helps protect air quality as well as contributes to efforts to deal with climate change.